Efficacy of istradefylline for gait disorders with freezing of gait in Parkinson's disease: A single-arm, open-label, prospective, multicenter study. (24th July 2019) - Iijima, Mutsumi; Orimo, Satoshi; Terashi, Hiroo; Suzuki, Masahiko; Hayashi, Akito; Shimura, Hideki; Mitoma, Hiroshi; Kitagawa, Kazuo; Okuma, Yasuyuki
ABSTRACT: Background : Gait disorders are common in Parkinson's disease patients who respond poorly to dopaminergic treatment. Blockade of adenosine A2A receptors is expected to improve gait disorders. Istradefylline is a first-in-class selective adenosine A2A receptor antagonist with benefits for motor complications associated with Parkinson's disease. Research design and methods : This multicenter, open-label, single-group, prospective interventional study evaluated changes in total gait-related scores of the Part II/III Movement Disorder Society-Unified Parkinson's Disease Rating Scale (MDS-UPDRS) and Freezing of Gait Questionnaire (FOG-Q) in 31 Parkinson's disease patients treated with istradefylline. Gait analysis by portable gait rhythmogram was performed. Results : MDS-UPDRS Part III gait-related total scores significantly decreased at Weeks 4–12 from baseline with significant improvements in gait, freezing of gait, and postural stability. Significant decreases in MDS-UPDRS Part II total scores and individual item scores at Week 12 indicated improved daily living activities. At Week 12, there were significant improvements in FOG-Q, new FOG-Q, and overall movement per 48 h measured by portable gait rhythmogram. Adverse events occurred in 7/31 patients. Conclusions : Istradefylline improved gait disorders in Parkinson's disease patients complicated with freezing of gait, improving their quality of life. No unexpected adverse drug reactions were identified. Trial registration : UMIN-CTR (UMIN000020288).